Ulusal ve Uluslararası Türk Judocularda Elpençe Kuvveti - Ceylan, Bayram; Öztürk, Furkan (Düzce Üniversitesi, 2022)
The aim of this study was to determine and compare maximal handgrip strength (HGS) of international and national level judo athletes. Eighteen international and 16 national level judo athletes voluntarily participated in this study. After anthropometric measurements, athletes performed the maximal isometric HGS test three times on each side with a 1-min interval between attempts. Independent sample T test was used to compare groups and Pearson correlation coefficient was calculated to determine the relationship between variables. Significance was set at p<0,05. There was significant difference in body mass, height, body mass index, right, left and sum relative maximal HGS between groups (p<0,05). No other significant difference was observed. As for correlations among variables, there were significant correlations between body mass and maximal HGS (p=0.00). Also, there were significant correlations between body mass index and maximal HGS (p=0,00). According to classificatory table, most of the athletes were classified as regular for right hand absolute and relative, left hand absolute and relative and sum absolute and relative maximal HGS. International-level judo athletes presented better maximal isometric HGS than national judo athletes given absolute power they produced while national judo athletes presented better results in relative HGS.

Bu çalışmanın amacı uluslararası ve ulusal seviyedeki judocuların maksimal el pençe kuvvetini belirlemek ve karşılaştırmaktır. Çalışmaya 18 uluslararası ve 16 ulusal seviyede erkek sporcu gönüllü olarak katıldı. Antropometrik ölçümler sonrasında sporcular 1 dakika ara ile her el için rastgele 3 kez maksimal el pençe kuvvet testini gerçekleştirdi. Grupların performanslarını karşılaştırmak için bağımsız örneklemlerde T test kullanılırken, değişkenler arasındaki ilişkiyi belirlemek için Pearson korelasyon testi kullanıldı. Analamlılık düzeyi p<0,05 olarak kabul edildi. Gruplar arasında vücut ağırlığı, boy, vücut kütle indeksi, sağ, sol ve toplam rölatif el pençe kuvvetinde anlamlı farklılık tespit edildi (p<0,05). değişkenler arasındaki ilişki incelendiğinde, vücut ağırlığı ve vücut kütle indeksi ile maksimal el pençe kuvveti arasında anlamlı ilişki tespit edildi (p=0,00). Sınıflandırma tablosu ile değerlendirildiğinde, sporcuların çoğu sağ mutlak ve rölatif, sol mutlak ve rölatif ve toplam mutlak ve rölatif el pençe kuvvetinde sıradan olarak sınıflandırıldı. Rölatif el pençe kuvveti düşünüldüğünde, uluslararası seviyedeki sporcular ulusal seviyedeki sporculardan daha iyi performans ortaya koydu, ancak ulusal seviyedeki sporcular rölatif performansta daha iyi sonuçlar ortaya koymuştur
Keywords: Egzersiz ve Spor Bilimleri; strength; combat sports; men athletes; performance; kuvvet; mücadele sporları; erkek sporcular; performans; Sports Science and Exercise